Anti-Pseudomonas aeruginosa antibody detection in patients with bronchiectasis without cystic fibrosis. Issue 9 (1st September 2001) - Caballero, E; Drobnic, M-E; Pérez, M-T; Manresa, J-M; Ferrer, A; Orriols, R
Abstract : BACKGROUND: Pseudomonas aeruginosa is a frequent cause of infection in patients with bronchiectasis. Differentiation between non-infected patients and those with different degrees of P aeruginosa infection could influence the management and prognosis of these patients. The diagnostic usefulness of serum IgG antibodies against P aeruginosa outer membrane proteins was determined in patients with bronchiectasis without cystic fibrosis. METHODS: Fifty six patients were classified according to sputum culture into three groups: group A (n=18) with no P aeruginosa in any sample; group B (n=18) with P aeruginosa alternating with other microorganisms; and group C (n=20) with P aeruginosa in all sputum samples. Each patient had at least three sputum cultures in the 6 months prior to serum collection. Detection of antibodies was performed by Western blot and their presence against 20 protein bands (10–121 kd) was assessed. RESULTS: Antibodies to more than four bands in total or to five individual bands (36, 26, 22, 20 or 18 kd) differentiated group B from group A, while antibodies to a total of more than eight bands or to 10 individual bands (104, 69, 63, 56, 50, 44, 30, 25, 22, 13 kd) differentiated group C from group B. When discordant results between the total number of bands and the frequency of P aeruginosa isolation were obtained, the follow up of patients suggested that the former, in most cases, predicted chronic P aeruginosa colonisation. CONCLUSION: In patients with bronchiectasis the degree of P aeruginosa infection can be determined by the number and type of outer membrane protein bands indicating which serum antibodies are present.